Gambaran Faktor-Faktor Penyebab Terjadinya Perilaku Bullying pada Anak - Novi Herawati; Deharnita Deharnita (Ners Jurnal Keperawatan, 2019)
Bullying is a part of the child's aggressive behavior repeatedly towards his friends or other students that causes victims. Persecuted even on the Playground by Richard Werly in Liberation magazine in Japan at 2001, 10% of students who were stressed due to bullying had already committed at least one suicide attempt. Data of KPAI that from 2011 to 2015 at least 1,850 cases of violence (bullying) occurred at school and outside of school. The research is descriptive, to describe the causes of bullying behavior in children at Solok City Junior High School 2 in 2018. The population was 381 people, with a simple random sampling technique with a sample of 79 people. Data collection with questionnaire at  May 22-28 2018, with  univariate analysis. The results obtained were more than 70.9% of respondents doing forms of physical bullying in the form of hitting, more in part (58.2%) verbally in the form of dubbing, more in part (78.5%) mentally in silence (not care), the cause of bullying behavior from family factors is more partial (82.3%) because of the noise at home, from school factors, less (46.8%) ignore problems between schools, from peer factors more in part (77.2%) because friends like taunting other friends. It is expected that the school especially BK teachers can give extra attention to the behavior of students in schools to prevent bullying occurring in school. Keyword: students, bullying, causative factors